2019
DOI: 10.1016/j.stemcr.2019.04.023
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 Signaling Promotes Murine and Human Hematopoietic Regeneration following Ionizing Radiation

Abstract: Hematopoietic stem and progenitor cells (HSPCs) depend on regulatory cytokines from the marrow microenvironment. From an unbiased cytokine screen of murine marrow supernatants, we identified CC motif chemokine ligand 5 (CCL5) as an endothelial cell-secreted hematopoietic growth factor. Following treatment with CCL5, hematopoietic regeneration is accelerated and survival is prolonged after radiation. In mice with deletion of Ccr5, hematopoietic regeneration is delayed compared to control mice. Deletion of Ccr5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…The results indicated that the concentration of IFN-γ were significantly elevated in the infertile CCL5 was an important chemokine expressed by hematopoietic and non-hematopoietic cell. [35][36][37] CCL5 expression was associated with recruitment of CD8 + T lymphocytes in tumor and acute infection. [38][39][40] In addition, CCL5 can promote the cytotoxic ability of CD8 + T lymphocytes via cytokine production during systemic chronic lymphocytic choriomeningitis virus (LCMV) infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the concentration of IFN-γ were significantly elevated in the infertile CCL5 was an important chemokine expressed by hematopoietic and non-hematopoietic cell. [35][36][37] CCL5 expression was associated with recruitment of CD8 + T lymphocytes in tumor and acute infection. [38][39][40] In addition, CCL5 can promote the cytotoxic ability of CD8 + T lymphocytes via cytokine production during systemic chronic lymphocytic choriomeningitis virus (LCMV) infection.…”
Section: Discussionmentioning
confidence: 99%
“…CCL5 was an important chemokine expressed by hematopoietic and non‐hematopoietic cell 35–37 . CCL5 expression was associated with recruitment of CD8 + T lymphocytes in tumor and acute infection 38–40 .…”
Section: Discussionmentioning
confidence: 99%
“…RANTES is a pluripotent cytokine and plays important roles in inflammation; it is produced by a variety of cells, such as platelets, macrophages, eosinophils, fibroblasts, endothelium, epithelia and endometrial cells [ 33 ]. A recent study reported that injection of RANTES (as an endothelial cell-secreted hematopoietic growth factor) after 5 Gy TBI promoted hematopoietic cells and increased survival of C57BL/6 mice [ 34 ]. It is currently unclear why the RANTES levels went down in the intestine after radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…61 Interleukin 17 is a proinflammatory cytokine and supports the regeneration of hematopoietic progenitor cells and improves the survival of radiation damage. 62,63 Also, it promotes angiogenesis for neovascularization for injured tissue. 64 Interleukin 1α regulates the proliferation of hematopoietic stem cells and stimulates the growth factors required for hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%